Gramaticalização do item linguístico assim no português brasileiro : sua funcionalidade nos processamentos ideacional, interpessoal e textual - Bonfim, Fernando Sachetti (2014)
This paper aims at investigating the continuum of grammaticalization of the linguistic item assim in the current synchrony of Portuguese language. That was reached by means of a corpus of spoken language belonging to FUNCPAR (Grupo de Pesquisas Funcionalistas do Norte/Noroeste do Paraná). In order to do so, the metafunctions proposed by Halliday (1985) in his Systemic-Functional Grammar were confronted to the principles of grammaticalization (TRAUGOTT & HEINE, 1991). By acting that way, the central goal was to confirm the hypothesis according to which the least grammaticalized usages of assim, since they are more semantically-based, would perform predominantly ideational function; equally, the most grammaticalized usages, since they are less semantically-based, would perform predominantly interpersonal or expressive function. That hypothesis was confirmed and, besides, the following topics were also investigated: (i) the cognitive functionality (GIVÓN, 1989; URBANO, 2003, apud PRETI, 2003) of some usages of assim (as fórico textual and as discourse marker (DM)); (ii) the syntactic-argumentative positions occupied by the DM assim, which led to the proposal of two patterns of usage for that DM; and (iii) the participation of the DM assim in the establishment of rhetorical relations in a text (MANN & THOMPSON, 1988), among which the involvement of the item was more productive in the relations of elaboration, preparation and restatement. In short, what was pursued was to describe the multi-functionality of assim to the Portuguese speakers of North/Northeast of Paraná.